When do you realize that value is built? the co-creation of value in the experience of clients in financial services - Oliveira, Caroline Lujan de (2024)
Study purpose: The objective of this study was to propose the adaptation of the theoretical model of value co-creation, applied to financial services. Methodology/Approach: With a quantitative-explanatory approach and a Survey strategy, the data was collected through a questionnaire (Google Forms) administered to customers of financial services. Descriptive and inferential statistical analyses were conducted using IBM SPSS Amos 24.0.0. Main findings: The adjusted value co-creation theoretical model for financial services was accepted and the indices fit positively in the reference values ​​of structural equation modeling. Theoretical/methodological contributions: The analysis of the value co-creation process applied to financial services was expanded, and new variables that contribute to the value co-creation process were identified. Relevance/originality: The study highlights the presence of factors that are considered essential for the perception of value co-creation, presented within the interactive platform of capabilities and resources that have been suggested as metrics for the scaling of the available model, thereby aiding data collection and empirical testing in future research.